Lactobacillus protects the integrity of intestinal epithelial barrier damaged by pathogenic bacteria - Yu, Qinghua; Yuan, Lixia; Deng, Jun; Yang, Qian (Frontiers in Cellular and Infection Microbiology, 2015)
Pathogens invade intestinal mucosal barrier through phagocytosis of antigen presenting cells (dendritic cell, microfold cells), or through the invasion into the intestinal epithelial directly. Some pathogens could damage the cell junction between epithelial cells and use the paracellular pathway as an entrance to invade. Moreover, some Lactobacillus could inhibit the adhesion of the pathogens and protect the integrity of the cell junction and mucosal barrier. This research focused on the potential therapeutic effect of Lactobacillus fructosus (L. fructosus) C2 to attenuate ETEC K88 or S. typhimurium SL1344 induced changes to mucosal barrier. The results demonstrated that treatment of polarized Caco-2 cells with L. fructosus C2 reduced the permeation of dextran, and expression of IL-8, p-ERK and p-JNK when cells were infected with pathogenic bacteria. The findings indicated that L. fructosus C2 exerted a protective effect against the damage to the integrity of Caco-2 cells by ETEC or S. typhimurium infection.